Determining Electric Fields in Thunderclouds With the Radiotelescope LOFAR - Trinh, T. N.G.; Scholten, O.; Buitink, S.; Ebert, U.; Hare, B. M.; Krehbiel, P. R.; Leijnse, H.; Bonardi, A.; Corstanje, A.; Falcke, H.; Huege, T.; Hörandel, J. R.; et al. (Journal of Geophysical Research: Atmospheres, 2020)
An analysis is presented of electric fields in thunderclouds using a recently proposed method based on measuring radio emission from extensive air shower events during thunderstorm conditions. This method can be regarded as a tomography of thunderclouds using cosmic rays as probes. The data cover the period from December 2011 till August 2014. We have developed an improved fitting procedure to be able to analyze the data. Our measurements show evidence for the main negative-charge layer near the −10° isotherm. This we have seen for a winter as well as for a summer cloud where multiple events pass through the same cloud and also the vertical component of the electric field could be reconstructed. On the day of measurement of some cosmic-ray events showing evidence for strong fields, no lightning activity was detected within 100 km distance. For the winter events, the top heights were between 5 and 6 km, while in the summer, typical top heights of 9 km were seen. Large horizontal components in excess of 70 kV/m of the electric fields are observed in the middle and top layers.
CRIS-Team Scopus Importer:2020-05-08